Stroke and the need for immediate assistance at the place of onset: the future of mandatory training for lay people in Italy - Stirparo, G.; Pireddu, R.; Kacerik, E.; Scognamiglio, T.; Andreassi, A.; Sechi, G. M.; Zoli, A.; Signorelli, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Lay training is essential to manage emergencies properly, although patients or bystanders need increased recognition of medical urgencies such as strokes. In Italy, as defined by Legislative Decree 81/08, all companies must train employees responsible for correctly recognizing and managing medical emergencies. Our study aims to evaluate the characteristics of medical emergencies concerning patients with a possible stroke in the Lombardy Region.Methods. A retrospective observational study was conducted. All missions performed by Regional Agency for Emergencies and Urgencies (Agenzia Regionale Emergenza Urgenza – AREU) in which the patient presented a possible stroke, recorded in the SAS-Areu database, were analyzed. The study period was from January 1, 2019, to December 31, 2019.Results. 10,201 patients with possible stroke were rescued, of whom only 540 (5.3%) occurred in workplaces. In workplaces, the percentage of males with a possible stroke was higher (62.2% vs 45.2%; p